The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/polb.22345
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling the effects of crystallinity and orientation on the shear piezoelectricity of polylactic acid

Abstract: Shear piezoelectricity has been shown to be linearly proportional to the product of polymer crystallinity and orientation. However, investigations concerning the singular and cumulative effects of these parameters are incomplete since these studies relied exclusively on using orientation to alter crystallinity. In this research, polylactic acid (PLA) samples were fabricated by a dual drawing/annealing process to expand the investigation into the relationship between crystallinity, orientation, and shear piezoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…After reaching 220°C, the sample was held at this temperature for 5 min before ramping down to 0°C at a ramp rate of 20°C/min. %Crystallinity of the samples were calculated using the equation %Crystallinity=ΔHfnormalobsΔHf=ΔHmΔHcΔHf where ΔHm,ΔHc and ΔHfo (= 93.1 J/g) are enthalpy of melting, enthalpy of crystallization and enthalpy of fusion for 100% crystalline PLA, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reaching 220°C, the sample was held at this temperature for 5 min before ramping down to 0°C at a ramp rate of 20°C/min. %Crystallinity of the samples were calculated using the equation %Crystallinity=ΔHfnormalobsΔHf=ΔHmΔHcΔHf where ΔHm,ΔHc and ΔHfo (= 93.1 J/g) are enthalpy of melting, enthalpy of crystallization and enthalpy of fusion for 100% crystalline PLA, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…where DH m ; DH c and DH o f (5 93.1 J/g) [19] are enthalpy of melting, enthalpy of crystallization and enthalpy of fusion for 100% crystalline PLA, respectively.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…This has been attributed to the displacement of the C=O bond in PLLA in response to mechanical stress leading to generation of a net dipole moment and charge [145][146][147]. PLLA has been used to fabricate films, fibres and rods with piezoelectric behaviour [148][149][150][151] and it has been observed that crystallinity and polymer orientation play key role in piezoelectric characteristic [152]. It presents an additional advantage of fabricating degradable scaffolds [153][154][155].…”
Section: Pllamentioning
confidence: 99%
“…Due to its helix structure, PLLA exhibits shear piezoelectricity [ 10 ]. When PLLA is oriented and crystalline, usually as fibers or films, the chains are strained, the molecular dipoles are aligned, and a voltage difference is observed [ 11 ]. Such a structure, formulated as a piezoelectric scaffold, can be applied for piezo-stimulation and promoting cell proliferation.…”
Section: Introductionmentioning
confidence: 99%